Targeted optimization of central carbon metabolism for engineering succinate production in Escherichia coli. Issue 1 (December 2016) - Zhao, Ying; Wang, Chang-Song; Li, Fei-Fei; Liu, Zhen-Ning; Zhao, Guang-Rong
Abstract Background Succinate is a kind of industrially important C4 platform chemical for synthesis of high value added products. Due to the economical and environmental advantages, considerable efforts on metabolic engineering and synthetic biology have been invested for bio-based production of succinate. Precursor phosphoenolpyruvate (PEP) is consumed for transport and phosphorylation of glucose, and large amounts of byproducts are produced, which are the crucial obstacles preventing the improvement of succinate production. In this study, instead of deleting genes involved in the formation of lactate, acetate and formate, we optimized the central carbon metabolism by targeting at metabolic node PEP to improve succinate production and decrease accumulation of byproducts in engineeredE. coli . Results By deletingptsG, ppc, pykA, maeA andmaeB, we constructed the initial succinate-producing strain to achieve succinate yield of 0.22 mol/mol glucose, which was 2.1-fold higher than that of the parent strain. Then, by targeting at both reductive TCA arm and PEP carboxylation, we deletedsdh and co-overexpressedpck andecaA, which led to a significant improvement in succinate yield of 1.13 mol/mol glucose. After fine-tuning ofpykF expression by anti-pykF sRNA, yields of lactate and acetate were decreased by 43.48 and 38.09 %, respectively. The anaerobic stoichiometric model on metabolic network showed that the carbon fraction to succinate of engineered strains was significantly increased at the expense of decreased fluxes to lactate and acetate. In batch fermentation, the optimized strain BKS15 produced succinate with specific productivity of 5.89 mmol gDCW−1 h−1 . Conclusions This report successfully optimizes succinate production by targeting at PEP of the central carbon metabolism. Co-overexpressingpck -ecaA, deletingsdh and finely tuningpykF expression are efficient strategies for improving succinate production and minimizing accumulation of lactate and acetate in metabolically engineeredE. coli .